Whither agricultural in 2021 and beyond - Belasco, Eric J.; Glauber, Joseph W.; Smith, Vincent H. (American Enterprise Institute, 2021)
The past four years have been chaotic for US agriculture. Trade wars, initiated by the Don-ald Trump administration in 2017, and the 2020 COVID-19 pandemic have led to volatile domestic and international market conditions and considerable uncertainty about future prices and farm businesses’ financial situations. In response to lower prices result-ing from lost access to international markets and, on a shorter-term basis, pandemic-related supply chain disruptions, the Trump administration responded by sending unprecedented amounts of ad hoc disas-ter relief aid to farmers through two Market Facilita-tion Programs and the Coronavirus Food Assistance Program. However, the United States may well be on the cusp of major changes in agricultural policy, given the Joe Biden administration’s priorities, an upcoming farm bill (2023), and major changes in the leadership of key congressional committees, the United States Department of Agriculture, and the Environmental Protection Agency.